PERENCANAAN PROGRAM-PROGRAM PENGENTASAN KEMISKINAN DALAM PENCAPAIAN TARGET MDGs TAHUN 2015 DI KOTA BATU - Saiful Ludoni; Irwan Noor; Luqman Hakim (REFORMASI, 2016)
The purpose of this study is first, to describe and analyze the poor households economics condition and the existing programs for poverty alleviation to reach Millenium Development Goals targets in Batu City on 2015. Secondly, to describe and analyze the available options for the SKPD (government’s Agency) in planning the programs for city’s poverty eradication Strategy to reach the MDGs target 1: eradicate poverty and extreme hunger. The conclusion of this study are as follows: (1) the planning of programs on poverty eradication strategy is designed with the top down and bottom up approaches to implement the economics, social and ecology developments in eradicating poverty and extreme hungers in batu city. (2) Programs and activities to eradicate poverty in Batu City were prepared by Vision - Mission - Goals, the strategic issues that had been developed previously by United Nations through its Millenium Development Goals and also by the indonesian Government. The Batu City Government should keep up the good work on MDGs achievements and plan on both permanent and ad-interim poverty eradication programs, so the acceleration of targets achievement on MDGs 2015 and Sustainable Development Goals 2030 can be attained on time. (3) the supporting factor for the eradication of poverty in Batu city is the government’s longstanding commitment to eradicate poverty and extreme hunger, Recommendations that can be delivered to synchronize the implementation of poverty alleviation programs with mechanisms, procedures and rules of the municipality system are implemented by reviewing the planning of the programs for the city poverty eradication strategies and take a closer look to the problems and root causes of the poverty alleviation problems.